Case report: when art is faced with brain surgery: acute change in creative style in a painter after glioma resection - Duffau, Hugues (Frontiers in Oncology, 2024)
Background Strong interactions between art and health are well-known. While advances in brain surgery resulted in an improved preservation of sensorimotor, visuospatial, language and cognitive functions, creative abilities received less attention. However, creativity may represent a critical issue to resume an optimal quality of life, especially in artists. Here, a unique case of sudden change in creative style in a painter who underwent glioma resection is described. This prompts to explore further creative thinking and its clinical implications in routine practice.Methods A 36-year-old right-handed woman experienced inaugural seizures, allowing the discovery of a right frontal lesion. The patient was a professional painter and did not complain about any decline in her creativity. The preoperative neurological examination was normal.Results Surgery was achieved with a maximal tumor resection through a frontal lobectomy. A WHO grade II oligodendroglioma was diagnosed. A regular surveillance was performed without adjuvant oncological treatment. The patient did not exhibit postoperative functional deterioration and she returned to normal activities including painting during 15 years. Remarkably, even though her creative activity was judged by the patient herself to be rich and satisfying, her style drastically changed from surrealism and mysticism to cubism whereas she was not able to explain why.This is the first report of acute modification of the painting style following frontal lobectomy for a low-grade glioma, supporting that brain resective surgery may impact creativity. While neglected for many decades, this complex human ability should be evaluated more regularly in neurosurgical practice, particularly in artists.